2007
DOI: 10.1128/ec.00169-07
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Number-Counting Factor Regulates Levels of a Novel Protein, SslA, as Part of a Group Size Regulation Mechanism in Dictyostelium

Abstract: Developing Dictyostelium cells form aggregation streams that break into groups of ϳ2 ؋ 10 4 cells. The breakup and subsequent group size are regulated by a secreted multisubunit counting factor (CF). To elucidate how CF regulates group size, we isolated second-site suppressors of smlA ؊ , a transformant that forms small groups due to oversecretion of CF. smlA ؊ sslA1(CR11) cells form roughly wild-type-size groups due to an insertion in the beginning of the coding region of sslA1, one of two highly similar gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 70 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…3G). Since glucose has been suggested to increase aggregation size, we measured intracellular levels of glucose (34,22). We found that glucose levels in amtA Ϫ cells were higher than those in wild-type cells (Fig.…”
Section: Strainsmentioning
confidence: 94%
“…3G). Since glucose has been suggested to increase aggregation size, we measured intracellular levels of glucose (34,22). We found that glucose levels in amtA Ϫ cells were higher than those in wild-type cells (Fig.…”
Section: Strainsmentioning
confidence: 94%
“…However, in Bayesian inference studies, T. nana has shown either a medium (rps16, Hong & Jury, 2011) or a slow (matK, Figure 2) evolutionary rate compared to the remainder of the genus. However, the generation time differences between T. nana and other Tricyrtis taxa are much less than for example between humans and Drosophila or Dictyostelium (Ehrenman et al, 2003;Gao et al, 2007;Hong, Qi, Brabant, Bosco, & Martinez, 2008) and may not be a significant factor in this case.…”
Section: Discussionmentioning
confidence: 84%
“…Three out of the five validated bacterial growth genes– abpC , smlA and pten , are involved in actin polymerization and cell motility [ 33 – 36 ]. One explanation for the enrichment of these genes is that the availability of preexisting knockout strains may be enriched with cell motility genes.…”
Section: Discussionmentioning
confidence: 99%